Home-based injury prevention program during COVID-19 lockdown reduced injuries during the remaining season in semi-professional football players - Razi, M.; Alizadeh, M. H.; Minoonejad, H.; Meyer, T. (British Journal of Sports Medicine, 2021)
Background The Covid-19 pandemic caused a forced lockdown longer than the normal annual season break in Iranian football leagues. Return to football after such a long break without organized team training might increase the rate of injuries.